Obtener las componentes del vector ortogonal a dos vectores en R3
1
U(-17, 8, -1), V(-4, 34, 10)
2
U(-2, -9, -20), V(-13, -27, -4)
3
U(13, 2, -12), V(-21, 3, -6)
4
U(3, 13, -6), V(-17, 8, -9)
5
U(25, -6, -12), V(18, 10, 3)
6
U(-18, 15, -22), V(10, 7, -9)
7
U(-7, 21, -10), V(-14, 37, -2)
8
U(17, 1, -5), V(2, 6, 22)
9
U(33, -7, -30), V(-1, -13, 34)
10
U(1, 25, 3), V(-18, 17, -7)
11
U(15, 10, -5), V(-10, 12, 14)
12
U(-9, 5, 10), V(5, -30, 3)
13
U(-21, -18, -27), V(22, -5, -22)
14
U(32, -3, -18), V(-29, -11, -6)
15
U(5, 25, -38), V(-17, 14, -25)
16
U(-8, 27, 32), V(0, 24, -3)
17
U = 19i - 4j + 14k, V = 9i + 7j + 14k
18
U = - 15i - 9j - 9k, V = - 5i - 11j + 19k
19
U = - 11i - 2j - 8k, V = - 3i + 2j + 17k
20
U = 9i + 19j + 19k, V = 13i + 20j + 9k
21
U = 15i + 8j - 20k, V = - 10i + 5j + 16k
22
U = 6i - 12j - 15k, V = 6i - 15j + 2k
23
U = - 15i + 6j - 5k, V = 18i + j - 17k
24
U = 14i - j + 20k, V = 11i + 5j - 8k
25
U = i - 11j + 15k, V = 13i - 16j + 13k
26
U = 9i + 4j + 8k, V = 17i - 6j - 9k
27
U = - 5i - 9j + 9k, V = - 13i + 20j + 4k
28
U = 8i - 13j + 12k, V = - 15i + 9j + 19k
29
U = - 15i + 15j + 5k, V = - 2i + 20j - 6k
30
U = 11i - 7j - 11k, V = 6i + 5j + 6k
31
U = 16i + 17j + k, V = - 14i - 19j + 16k
32
U = - 3i + 13j + k, V = 7i + 11j + k
33
U = - 13i + 11j - 19k, V = - 15i - 8j - 15k
34
U = - 4i + 7j - 5k, V = - 7i + 11j + 11k
35
U = 8i - 10j + 11k, V = - 9i - 13j + 3k
36
U = 13i + 16j - 5k, V = 12i + 10j + k
37
U = 8i + 3j + 19k, V = 5i + 17j + 6k
38
U = 8i - 13j - k, V = i - 10j - 16k
39
U = 10i + j + 8k, V = - 3i - 4j - k
40
U = - 15i - 7j + 4k, V = - 16i - 20j + 8k
41
U = - 4i - 17j - 12k, V = 11i + 18j - k
42
U = 20i - 2j - 12k, V = 16i + j - 16k
43
U = 11i - 5j - 17k, V = - 10i + 10j - 11k
44
U = 9i + 18j - 10k, V = - 7i - 11j - 3k
45
U = - 17i - 17j - 17k, V = 18i + 13j - 5k
46
U = 19i - 17j + 7k, V = 20i - 19j + 8k
47
U = - i - 15j + k, V = 2i + 12j - 14k
48
U = i - 8j + 8k, V = 10i - 15j + k
49
U = - 11i + 12j + 19k, V = 20i - 19j + 8k
50
U = - 4i + 8j + 6k, V = - i - 5j + 6k
51
U = 14i - 9j - k, V = 19i - 7j + 7k
52
U = - 20i - 20j - 14k, V = - 12i - 10j - 3k
53
U = 17i - 4j - 15k, V = 13i + 3j - k
54
U = 16i + 4j - k, V = - 18i - 9j + 15k
55
U = - 5i - 13j - 7k, V = - 10i + 10j + 5k
56
U = - 19i + 2j + k, V = - 19i - 2j - 8k
57
U = - 14i + 9j - 2k, V = - 4i + 2j - 12k
58
U = 20i + 20j + 5k, V = 10i - j + 6k
59
U = - 11i - 14j - 17k, V = 3i - 9j - 3k
60
U = 8i + 5j + 7k, V = 6i - 19j + 12k
61
U = - 2i + 3j + 8k, V = - 4i - 20j - 20k
|